The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s13011-021-00407-5
|View full text |Cite
|
Sign up to set email alerts
|

The validity and reliability of Persian version of smartphone addiction questionnaire in Iran

Abstract: Background Smartphone addiction is one of the most important forms of technology addiction that has attracted the attention of all countries around the world. Many studies have been conducted in Iran on cellphone addiction among different groups. There is a necessity to have a native scale for measuring smartphone addiction in particular. Therefore, this study aimed to localize the smartphone addiction questionnaire in Iran (in the Persian language). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Higher scores on this scale indicate greater dependence on smartphones, and a score of 99 or more mean smartphone addiction. Shaahmadi et al [20] reported that internal consistency and concurrent validity of the questionnaire were confirmed by Cronbach's alpha of 0.951. APS is a selfreporting 27-item questionnaire that was developed by Najarian et al in 1999 after testing on a sample of 395 students from Shahid Chamran University and the Islamic Azad University of Ahvaz.…”
Section: Instrumentsmentioning
confidence: 96%
“…Higher scores on this scale indicate greater dependence on smartphones, and a score of 99 or more mean smartphone addiction. Shaahmadi et al [20] reported that internal consistency and concurrent validity of the questionnaire were confirmed by Cronbach's alpha of 0.951. APS is a selfreporting 27-item questionnaire that was developed by Najarian et al in 1999 after testing on a sample of 395 students from Shahid Chamran University and the Islamic Azad University of Ahvaz.…”
Section: Instrumentsmentioning
confidence: 96%
“…Several theories and factors can help explain the mechanisms of behavioral addictions, including personality factors (Katz et al, 1973;Rubin, 1993;Ryan, Chester, Reece & Xenos, 2014;Wegmann & Brand;, family influences (Wampler et al, 1993), theories of uses and rewards (Armstrong et al, 2000;Cain et al, 2008;Campbell et al, 2007;Dambrun & Ricard, 2011;Ghassemzadeh et al, 2008;Goffman, 1956;Katz et al, 1973;Widyanto & Griffiths, 2011), neurophysiological influences (Nestler, 2013), operant conditioning (Delfabbro & Winefield, 1999;Dixon et al, 2006;Haw, 2008;Skinner 1974), and social learning theory (Bandura, 1986;Shaahmadi et al, 2021;Sherman et al, 2016;.…”
Section: Instagram Addictionmentioning
confidence: 99%